THE CONCEPT OF “WHITE - COLLAR” CRIME - Slamkov, Gjorgi; Stamevski, Vasko; Stamevska, Elizabeta (International Scientific Journal Vision, 2022)
Тhe term “white-collar” crime is synonymous with the full rage of frauds committed by business and government professionals. These crimes are characterized by deceit, concealment, or violation of trust and are not dependent on the application or threat of physical force or violence. Within the “white-collar” crime included all forms of economic and financial crime, such as bribery, tax evasion, falsification of tax books, fake bankruptcies, etc, that is, a group of crimes that can be committed by privileged perpetrators by exploiting their own position, reputation, power, and influence. The motives behind the commission of “white-collar” crimes primarily are the wish for control in society, fear and anxiety of dwindling from the social status, lack of social consciousness and integrity, weak and ineffective internal controls of organizations and departments, greed and hunger of wealth, monetary and financial gains and ineffective and ineffectual corporate culture in economy.